(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
E-commerce is important branch in economics and it is the fastest growing retail market, expected to reach more than 250 billion EUR in 2017. Sucessfull online business make impact on customer behaviour. The aim of the article is to research customer behaviour doing online shopping. This article contain the analyse of theoretical approaches to consumer behaviour and analyse of customer survey results to find out the Latvia’s customer behaviour doing online shopping .